Simulation of Phase Change Materials Usage to Inhibit Temperature Rise of Solar Panel Wall - Nuran Zaini, Ilman
Solar energy is one type of renewable energy that is widely used today. Technology commonly used in harnessing solar energy is solar cell/ photovoltaic (PV) that convert solar energy into electricity. One challenge in solar cell technology is low efficiency and efficiency reduction as temperature increases. Phase change materials (PCM) can be used to inhibit the rise in solar cell temperature. Latent heat storage capability of the PCM, which is produced when the PCM melts, is responsible to keep solar cell temperature low. In this research, computational simulation using FLUENT software is used to study effects of phase change materials usage in the solar cell. Coconut oil and palm oil were used as PCM in this research. From the simulation result, it can be seen that surface temperature of PV with PCM is lower than that of normal PV. The difference of average surface temperature between both PV is 3.6oC. The use of palm oil as a phase change material is more effective than coconut oil because its melting temperature is higher than ambient temperature. In addition, the optimum thickness of the phase change material used in solar panels is 80 mm. From the results of this study, it can be concluded that the use of phase change materials could inhibit the rise in wall temperature of solar panels.